Konstruksi Pengaturan Teknologi Telesurgery di Indonesia dalam Era Industri 4.0 - CITRA AYU DESWINA MAHARANI (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
Telesurgery in Indonesia represents a tangible manifestation of the Fourth Industrial Revolution in the health sector, expanding access to surgical services while simultaneously introducing legal challenges that require urgent regulatory attention. This study aims to examine the implications of telesurgery and develop a legal framework capable of ensuring legal certainty, patient safety and professional accountability. Despite its advantages such as improved efficiency, surgical precision and equitable access to specialist care telesurgery also presents significant risks, including cybersecurity threats, unclear liability structures, the absence of standardized digital informed consent procedures and the potential leakage of sensitive medical data. To address these issues, this research employs a normative legal method using statutory, conceptual and comparative approaches, analyzing relevant legislation such as the Health Act, Medical Practice Act, Electronic Information and Transactions Act and Personal Data Protection Act, along with academic literature and international practices. The findings reveal that the current Indonesian legal framework does not specifically regulate the technical and procedural aspects of telesurgery, resulting in a normative gap. Therefore, this study recommends the establishment of a Government Regulation as a lex specialis governing operational standards, network security, medical personnel certification and data governance, supplemented by a Ministerial Regulation to ensure patient protection and legal certainty in telesurgery practices in Indonesia.